A century of sexual abuse victimisation: A birth cohort analysis. (February 2021) - Fanslow, Janet; Hashemi, Ladan; Gulliver, Pauline; McIntosh, Tracey
Abstract: This study examined changes in the reported prevalence of adult and child sexual abuse over the last century and explored how changes in social and political circumstances may have affected rates. Data from two population-based face-to-face surveys conducted in New Zealand (samples of 2855 women in 2003 and 1464 women in 2019) were used to produce birth cohort prevalence estimates of three forms of sexual abuse including by an intimate partner (lifetime and 12-month), by non-partners, and child sexual abuse. A timeline of major population influences that might be associated with violence occurrence was developed. There were no changes in reported lifetime intimate partner sexual abuse prevalence estimates found over the past century. The most recent birth cohort reported the lowest rates of 12-month prevalence estimates for intimate partner sexual abuse, lifetime rates of non-partner sexual abuse, and also suggest lower reported rates of child sexual abuse. Macro-social events including feminist movements, changes in legislation, and an increase in public awareness might have contributed to women's awareness about the non-acceptability of violent behaviour, and their ability to leave relationships after violence has occurred. This may have contributed to the small recent decreases in reported 12-month rate of sexual IPV and CSA, as women's ability to leave relationships may be protective for their children. The recent decrease in reported non-partner sexual violence may also be attributed to women's greater awareness of, and agency to avoid sexual abuse. The lack of change for the lifetime prevalence of sexual IPV over the past century highlights the need for ongoing prevention efforts. While recent reductions in reported rates of child and adult sexual abuse are encouraging, even reduced rates are high and warrant sustained implementation of prevention policies and programs. Highlights: Birth cohort analysis was used to explore changes in sexual abuse prevalence. No change in lifetime intimate partner sexual abuse prevalence estimates was found. Younger cohorts had lower rates of non-partner and child sexual abuse. Macro-social events may have contributed to observed changes in prevalence rates. Reduced rates are still high and warrant sustained prevention efforts.